INCREASE EMPLOYMENT AND WELFARE OF RURAL DWELLERS - Mamur Tairovich Saidmurodov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the organizational and economic indicators of the development of small business and private entrepreneurship in the service sector. In addition, the subsequent adopted legal and regulatory documents on the development of the industry, their content and essence, and scientific recommendations are presented.